Модель периферійної бібліотеки в контексті сучасних культурних трансформацій - Корнєєва, Л. Л.; Ломоносов, М. В. (My University, 2017)
У статті розглядаються проблеми, які виникають перед сучасною бібліотекою. З'ясовується специфіка периферійної біблютеки. Аргументується розуміння бібліотеки як "третього місця".
The article deals with the problems that arise for the modern library. If earlier the library was the treasury of knowledge, in our time it loses this functbn as the main one. The specificity of the peripheral library is analyzed. Modem technobgy allows you to receive information anywhere, even in the province. But for the province there is a more acute problem of cultural bisure and communication. The fulfillment of these needs can become a new opportunity for the peripheral library. The article argues the understanding of the library as a "third place". 'Third place" is a place where a person can be apart from home and work. This is a good chance for the preservatbn of the relevance of the peripheral library in our time.
Keywords: бібліотека; культурні трансформації; дозвілля; library; periphery; cultural transformations